Slurry for shortening freezing time of T joint in shield method contact channel and preparation method thereof
By using slurry of components such as graphene nanosheet powder in the shield method connection channel, the problems of poor stability of slurry at the T joint and the water and sand gushing are solved, and the effects of rapid solidification and stable connection are achieved.
Patent Information
- Application Number
- CN202411700486.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
The slurry at the T joint in the shield structure method is poor in stability and is easily diluted, resulting in difficult control of the reinforcement range, uneven reinforcement strength, poor sealing effect, and there is a risk of water and sand gushing during construction.
Using a slurry including graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener, and water reducing agent, the thermal conductivity of the slurry is improved by specific ratios and combinations. Solidification strength reduces freezing time and avoids water and sand gushing.
The stability and viscosity of the slurry are improved, and it is quickly filled and solidified, avoiding water and sand gushing, ensuring the stable connection of the T-joint and the stability of the structure.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shield tunnel construction materials, and in particular to a slurry used for shortening the freezing time of a T-joint in a shield tunneling communication channel and a preparation method thereof. Background Art
[0002] In recent years, the mechanical method of excavating subway inter-section communication channels has gradually become popular. As a type of mechanical method communication channel, the shield method communication channel has formed the key technologies of "weak reinforcement, strong support, machinability, full closure, balance, strict waterproofing, and intensiveness".
[0003] The "weak reinforcement" technology includes water-stopping reinforcement measures for the portal at the T-joint before removing the steel sleeve. T-joints are prone to serious safety accidents such as sudden water gushing. In previous construction cases, grouting methods were mostly used to ensure the water-stopping effect of the T-joint portal gap during the removal of the steel sleeve and the pouring of the portal. However, in the prior art, the stability of the grouting slurry is poor and it is easily diluted in muddy water, which makes the reinforcement range difficult to control and the reinforcement strength uneven, resulting in poor sealing effect, especially in soft soil formations with silt and silt sand confined aquifers; secondly, there is a greater risk of water and sand gushing during the construction process. It is necessary to ensure that the injected slurry can react quickly, reduce the reaction time, and quickly freeze the slurry at the portal to avoid the risk of water and sand gushing. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a slurry for shortening the freezing time of T-joints in shield tunneling communication channels and a preparation method thereof. The slurry of the present invention not only has a high thermal conductivity and can reduce the time at the T-joint, but also has a high strength after solidification.
[0005] The invention provides a slurry for shortening the freezing time of a T-joint in a shield tunneling communication channel. The slurry comprises graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, a thickener and a water reducer. The ratio of the graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, a thickener and a water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%) by mass, and the balance is water.
[0006] Furthermore, the particle size of the graphene nanosheet powder is less than 15 mm and greater than 5 mm.
[0007] Furthermore, the lime has a calcium content of not less than 95%.
[0008] Furthermore, the fineness modulus of the fine sand is 1.6-2.2.
[0009] Furthermore, the fly ash includes fly ash with a particle size of 2800 mesh to 3200 mesh.
[0010] Furthermore, the bentonite includes sodium-based bentonite with a particle size of 1400-1600 mesh.
[0011] Furthermore, the thickener includes one or more of carboxymethyl cellulose, gum arabic, polyvinyl alcohol, and polyvinyl pyrrolidone.
[0012] Furthermore, the water reducer includes FDN-C type naphthalene-based water reducer.
[0013] Further, the slurry includes graphene nanosheet powder, silicon carbide, lime with a calcium content of not less than 95%, fine sand with a fineness modulus of 1.6-2.2, fly ash with a particle size of 2800-3200 mesh, sodium-based bentonite with a particle size of 1400-1600 mesh, thickener, and FDN-C type naphthalene water reducer. By mass, the graphene nanosheet powder, silicon carbide, lime with a calcium content of not less than 95%, and fineness modulus of 1.6- The ratio of 2.2 fine sand, fly ash with a particle size of 2800 mesh-3200 mesh, sodium bentonite with a particle size of 1400 mesh-1600 mesh, thickener, and FDN-C naphthalene-based water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%), and the balance is water.
[0014] The present invention also provides a method for preparing a slurry for shortening the freezing time of T-joints in a shield tunneling communication channel. The preparation method comprises respectively weighing graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener, and water reducer. The ratio of the graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener, and water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%) by mass, and the balance is water. The mixture is mixed evenly to obtain the slurry of the present invention.
[0015] Furthermore, the particle size of the graphene nanosheet powder is less than 15 mm and greater than 5 mm.
[0016] Furthermore, the lime has a calcium content of not less than 95%.
[0017] Furthermore, the fineness modulus of the fine sand is 1.6-2.2.
[0018] Furthermore, the fly ash includes fly ash with a particle size of 2800 mesh to 3200 mesh.
[0019] Furthermore, the bentonite includes sodium-based bentonite with a particle size of 1400-1600 mesh.
[0020] Furthermore, the thickener includes one or more of carboxymethyl cellulose, gum arabic, polyvinyl alcohol, and polyvinyl pyrrolidone.
[0021] The present invention also provides the use of the slurry for shortening the freezing time of T-joints in shield tunneling communication channels in filling T-joints.
[0022] The embodiments of the present invention have the following technical effects: 1. The slurry obtained by the present invention first has good stability and good viscosity, and will not cause solid-liquid separation. Secondly, it also has high thermal conductivity. When the slurry is pumped into a specified position, it can be quickly filled and quickly solidified to avoid the risk of water and sand gushing. Finally, the slurry obtained by the present invention can quickly fill the T-joint gap and the surrounding soil after solidification, which is beneficial to the stability of the shield tunnel structure. In addition, the solidified slurry also has high mechanical strength.
[0023] 2. In the present invention, the technical effect of the present invention is achieved through the mutual cooperation between the components in the slurry. Graphene nanosheet powder has excellent thermal properties, which can not only increase the fluidity of the slurry, but also improve the thermal conductivity of the slurry. The improvement of thermal conductivity can accelerate the reaction speed, promote the rapid release of heat in the slurry, and reduce the cracks formed after the slurry is frozen due to excessive reaction heat. Silicon carbide can partially replace graphene nanosheet powder, form a thermally conductive network structure in the slurry, assist graphene nanosheet powder in improving the thermal conductivity of the slurry, and also improve the support strength of the slurry after freezing. Lime and fly ash react with each other to produce new hydration products - colloidal, filamentous, fibrous and needle-shaped calcium silicate hydrates. These hydration products can be filled in the pores of the thermal conductive network structure, increasing the density and impermeability of the slurry after solidification, and can also improve the viscosity and fluidity of the grouting slurry, which is conducive to rapid and full filling, preparing for the rapid solidification of the slurry, so that the slurry can be fully filled in the gaps after solidification, and ensuring that the solidified slurry can be stably connected to the T-joint. Graphene nanosheet powder also has strong activity and can promote the lime reaction of fly ash, which is conducive to improving the reaction speed of the slurry. The thickener and water reducer can reduce the water absorption capacity of the slurry under the synergistic effect, and improve the viscosity of the slurry, thereby reducing the state of solid-liquid separation, thereby improving the stability of the slurry, making the strength of the slurry after the final solidification more uniform, and making the plugging effect better. Fine sand can further fully fill the pores forming the thermal conductive network structure, which is conducive to improving the strength of the solidified slurry. Bentonite contains silicate and aluminate, which can react with silicate ions in lime to form a gel, thus helping to increase the strength of the slurry after molding.
[0024] 3. The method for obtaining slurry of the present invention is simple and easy to implement, which is conducive to industrial production. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0026] In the first aspect, some embodiments of the present invention provide a slurry for shortening the freezing time of T-joints in a shield tunneling communication channel, wherein the slurry comprises graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener, and water reducer. The ratio of the graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener, and water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%) by mass, and the remainder is water.
[0027] In some embodiments, the graphene nanosheet powder has a particle size less than 15 mm and a particle size greater than 5 mm.
[0028] In some embodiments, the lime has a calcium content of not less than 95%.
[0029] In some embodiments, the fineness modulus of the fine sand is 1.6-2.2.
[0030] In some embodiments, the fly ash includes fly ash with a particle size of 2800 mesh to 3200 mesh.
[0031] In some embodiments, the bentonite comprises sodium bentonite having a particle size of 1400-1600 mesh.
[0032] In some embodiments, the thickener includes one or more of carboxymethyl cellulose, gum arabic, polyvinyl alcohol, and polyvinyl pyrrolidone.
[0033] In some embodiments, the water reducer includes FDN-C naphthalene-based water reducer.
[0034] In some embodiments, the slurry includes graphene nanosheet powder, silicon carbide, lime with a calcium content of not less than 95%, fine sand with a fineness modulus of 1.6-2.2, fly ash with a particle size of 2800-3200 mesh, sodium-based bentonite with a particle size of 1400-1600 mesh, thickener, and FDN-C type naphthalene water reducer. By mass, the graphene nanosheet powder, silicon carbide, lime with a calcium content of not less than 95%, and fineness modulus of 1.6-2.2 are The ratio of 6-2.2 fine sand, fly ash with a particle size of 2800 mesh-3200 mesh, sodium bentonite with a particle size of 1400 mesh-1600 mesh, thickener, and FDN-C naphthalene-based water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%), and the balance is water.
[0035] In the second aspect, some embodiments of the present invention also provide a method for preparing a slurry for shortening the freezing time of T-joints in a shield tunneling communication channel, the preparation method comprising respectively weighing graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener, and water reducer, and the ratio of the graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener, and water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%) by mass, and the balance is water, and the mixture is mixed evenly to obtain the slurry of the present invention.
[0036] In some embodiments, the particle size of the graphene nanosheet powder is less than 15 mm and greater than 10 mm.
[0037] In some embodiments, the lime has a calcium content of not less than 95%.
[0038] In some embodiments, the fineness modulus of the fine sand is 1.6-2.2.
[0039] In some embodiments, the fly ash includes fly ash with a particle size of 2800 mesh to 3200 mesh.
[0040] In some embodiments, the bentonite comprises sodium bentonite having a particle size of 1400-1600 mesh.
[0041] In some embodiments, the thickener includes one or more of carboxymethyl cellulose, gum arabic, polyvinyl alcohol, and polyvinyl pyrrolidone.
[0042] It should be noted that the terms used in the present invention are only for describing specific embodiments, rather than limiting the scope of the present application. As shown in the present specification, unless the context clearly indicates an exception, the words "one", "a", "a kind of" and / or "the" do not specifically refer to the singular, but may also include the plural. The terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or device. In the absence of more restrictions, the elements defined by the sentence "include one..." do not exclude the presence of other identical elements in the process, method or device including the elements.
[0043] It should also be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. Unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", etc. should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0044] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.
Claims
1. A slurry for shortening the freezing time of T-joints in shield tunneling communication channels, characterized in that: The slurry includes graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener and water reducer. By mass, the ratio of graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener and water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%), and the balance is water.
2. The slurry according to claim 1, characterized in that The particle size of the graphene nanosheet powder is less than 15 mm and greater than 5 mm.
3. The slurry according to claim 1, characterized in that The lime has a calcium content of not less than 95%.
4. The slurry according to claim 1, characterized in that The fineness modulus of the fine sand is 1.6-2.
2.
5. The slurry according to claim 1, characterized in that The fly ash includes fly ash with a particle size of 2800 meshes to 3200 meshes.
6. The slurry according to claim 1, characterized in that The bentonite includes sodium-based bentonite with a particle size of 1400-1600 meshes.
7. The slurry according to claim 1, characterized in that The thickener includes one or more of carboxymethyl cellulose, gum arabic, polyvinyl alcohol, and polyvinyl pyrrolidone; The water reducer includes FDN-C type naphthalene-based water reducer.
8. The slurry according to claim 1, characterized in that The slurry comprises graphene nanosheet powder, silicon carbide, lime with a calcium content of not less than 95%, fine sand with a fineness modulus of 1.6-2.2, fly ash with a particle size of 2800-3200 mesh, sodium-based bentonite with a particle size of 1400-1600 mesh, thickener, and FDN-C type naphthalene water reducer. The graphene nanosheet powder, silicon carbide, lime with a calcium content of not less than 95%, and fineness modulus of 1.6-2.2 are calculated by mass. The ratio of fine sand of 2, fly ash with a particle size of 2800 mesh-3200 mesh, sodium bentonite with a particle size of 1400 mesh-1600 mesh, thickener, and FDN-C naphthalene-based water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%), and the balance is water.
9. A method for preparing a slurry for shortening the freezing time of a T-joint in a shield tunneling communication channel according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: respectively weighing graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener and water reducer, wherein the ratio of the graphene nanosheet powder, silicon carbide, lime, fine sand, fly ash, bentonite, thickener and water reducer is (0.5%-3%): (1%-10%): (2%-8%): (40%-50%): (15%-25%): (2%-6%): (0.05%-0.2%): (0.02%-1%) by mass, and the balance is water, and the mixture is mixed uniformly to obtain the slurry of the present invention.